RELIGIOUS DIFFERENCE AND THE COMMON GOOD: REFLECTION ON TOLERATION AND PARTICIPATION IN CONTEMPORARY AMERICA AND INDONESIA - Muhamad Ali (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2022)
This paper seeks to discuss the extent to which religious differences can contribute to the promotion of the common good. It asks if the religious difference is sufficient for the states and the societies to attain the common good across religious and ethical persuasions in multi-faith countries such as America and Indonesia. It is primarily an ethical-philosophical question but is also related to historical, sociological, anthropological, and political contexts. For many religious people, religious particularity and distinction – including its truth and superiority claims – is a significant element of identity and sense of morality, but religious difference alone is insufficient for attaining the common good. Religions provide motivations to act good or evil. Religions offer rich resources, be doctrinal, narrative, experiential and emotional, ethical, legal, social, material, or political, but because there are many, often conflicting religious and ethical values from within the same and across religious traditions, it is not enough for everyone to share their beliefs and accept each other’s exclusive claims. For religions to help improve the public good, religious agents have to negotiate their particular and distinct identities and universal moralities and reinterpret their beliefs and norms contextually in light of the plural societies in which they live. The governments should also allow multiple voices, including the religious, by ensuring toleration, freedom of conscience and worship, and right of assembly.